THE INFLUENCE OF CONSUMER PERCEPTION AND BRAND IMAGE ON THE PURCHASING INTEREST IN KILLINEY COFFEE SHOPS AMONG THE YOUNG GENERATION IN MEDAN - Riza Fanny Meutia; Sukaria Sinulingga; Beby Karina Fawzeea; Isfenti Sadalia (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2020)
This study aims to analyze the influence of consumer perception and brand image on buying interest in killiney coffee shops among the younger generation of Medan City, both partially and simultaneously. Furthermore, formulating appropriate policies and strategies to be implemented to improve the company. This research is categorized as a quantitative study with an associative method and using a questionnaire as a research instrument. The population in this study is the young generation aged 20-29 years who are in six outlets namely; Killiney Coffee Shop Tasbih, Killiney Coffee Shop Cemara Asri, Killiney Coffee Shop Sun Plaza, Killiney Coffee Shop Hermes Mall, Killieny Coffee Shop RS.USU, and Killiney Coffee Shop RCW. The sampling technique uses a non-probability sampling method that is accidental sampling with a total sample of 90 customers. The method used for hypothesis testing in this study is the method of multiple linear regression. Based on research that has been done, it is found that the elements of consumer perception of freshness, habitual facts, different flavor, and environment of shop simultaneously have a significant effect on buying interest in Killiney Coffee Shop among the younger generation in Medan. The Killiney Coffee Shop brand image has three elements consisting of a memorable brand, an easily recognizable brand, and the brand reputation simultaneously has a significant effect on buying interest in the Killiney Coffee Shop among the younger generation in Medan. And buying interest consisting of attention, interest, expectation of desire, and action has a partial and significant influence on consumer perceptions and the brand image of Killiney Coffee Shop among the younger generation in Medan. Keywords: Consumer Perception, Brand Image, Purchase Interest